Control and vibration analysis in dynamic system - Salim, Mohd Azli (Penerbit Universiti Teknikal Malaysia Melaka, 2019)
This book provides a good learning of fundamental concept on control and vibration in dynamic system. This book also briefly discovers example and practical problems in application with advanced tools and methodology in problem solving. The key features of this book is the numerous examples and application in active and passive control include system identification case studies from the engineering field. It is very useful and will be interesting for control and vibration practitioners to read and enhanced their understanding and knowledge.